2015
DOI: 10.1007/s11064-015-1525-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Neuroprotective Effect of Hesperidin on Aluminium Chloride Induced Alzheimer’s Disease in Wistar Rats

Abstract: The present study was aimed to evaluate the protective effect of hesperidin (Hes) on aluminium chloride (AlCl3) induced neurobehavioral and pathological changes in Alzheimeric rats. Intraperitonial injection of AlCl3 (100 mg/kg body weight) for 60 days significantly elevated the levels of aluminium (Al), activity of acetylcholinesterase (AChE) and protein expressions of amyloid precursor protein (APP), β amyloid (Aβ 1-42), β and γ secretases as compared to control group in hippocampus and cortex of rat brain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 53 publications
16
87
0
Order By: Relevance
“…Hesperidin at the dose of 100 mg/kg and silibinin (100 and 200 mg/kg) significantly prevented the AChE elevation in the hippocampus. Our results are in accordance with the earlier studies with regards to the AChE inhibitor activity of hesperidin and silibinin [32,56,61,62]. Inhibition of AlCl 3 -evoked hippocampal AChE level by hesperidin and silibinin might be attributed to the improvement in the memory function.…”
Section: Discussionsupporting
confidence: 93%
“…Hesperidin at the dose of 100 mg/kg and silibinin (100 and 200 mg/kg) significantly prevented the AChE elevation in the hippocampus. Our results are in accordance with the earlier studies with regards to the AChE inhibitor activity of hesperidin and silibinin [32,56,61,62]. Inhibition of AlCl 3 -evoked hippocampal AChE level by hesperidin and silibinin might be attributed to the improvement in the memory function.…”
Section: Discussionsupporting
confidence: 93%
“…Bioflavonoid like HSP may inhibit induction of antioxidant enzyme activities and may play a role in tissue protection. Neuroprotective effect of hesperidin on aluminum chloride induced Alzheimer's disease in Wistar rats has been shown earlier [53]. Protective activities of HSP against microbes and several toxicities induced by oxidants, chemicals, toxins, chemotherapy, and radiotherapy agents has been shown earlier in in vitro and in vivo studies [54].…”
Section: Discussionmentioning
confidence: 97%
“…People residing nearby areas of the cement factories are more prone to Al exposure as dispersed particulate matters contain high amount of aluminum [6]. Previous animal studies from our laboratory indicated that Al-induced neuropathological, neurochemical and neurobehavioral changes similar to AD [4,7,8]. Since Al is an environmental neurotoxin, whose exposure is get increased due to lifestyle changes and implicated in the pathogenesis of AD, the current experiment was designed.…”
Section: Introductionmentioning
confidence: 99%